Different clinical characteristics and treatment strategies for patients with localized sinonasal diffuse large B cell lymphoma and extranodal NK/T cell lymphoma. Issue 1 (December 2017) - Huang, Yu; Jia, Bo; Jiang, Shiyu; Zhou, Shengyu; Yang, Jianliang; Liu, Peng; Gui, Lin; He, Xiaohui; Qin, Yan; Sun, Yan; Shi, Yuankai
Abstract The difference in clinical features and treatment outcomes between localized sinonasal diffuse large B cell lymphoma (SN-DLBCL) and sinonasal extranodal NK/T cell lymphoma (SN-ENKTL) is unclear. Therefore, we analyzed a total of 47 patients with localized SN-DLBCL and 211 patients with localized SN-ENKTL. The age distribution for these two subtypes is very distinct and the B symptoms were more common in SN-ENKTL. However, both SN-DLBCL and SN-ENKTL patients could achieve high overall response rate (ORR) and favorable prognoses. The 3-year overall survival (OS) rates for patients with SN-DLBCL and SN-ENKTL were 79.7 and 83.6% (p  = 0.707), and the 3-year progression-free survival (PFS) rates were 61.4 and 70.1% (p  = 0.294), respectively. For SN-DLBCL patients, chemotherapy followed by involved-field radiotherapy (IFRT) resulted in higher OS (83.7 vs 62.5%) and PFS (63.9 vs 50.0%) compared with chemotherapy alone, but the difference was not significant. No significant difference was found in the OS or PFS between radiotherapy alone and radiotherapy combined with chemotherapy for all patients with SN-ENKTL. But in extensive stage I and stage II SN-ENKTL patients, radiotherapy combined with chemotherapy could significantly improve the PFS (73.8 vs 50.0%) compared with radiotherapy alone. These results indicate that remarkable clinical disparities exist between localized SN-DLBCL and SN-ENKTL. However, different treatment strategies for them can result in similarly favorable prognoses.